Pengaruh Current Ratio, ROA, Total Assset Turnover Dan Debt To Equity Ratio Terhadap Harga Saham Pada Perusahaan Sektor Industri Dasar Dan Kimia Yang Terdaftar Di BEI - Riana Permata Sari; Mey Tisa Sihombing; Ruth Dameria Manurung; Deasy Arisandy Aruan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of the variable current ratio, ROA, total asset turnover and debt to equity ratio on stock prices. The research population obtained 67 companies selected using purposive sampling with certain criteria as many as 27 companies. The type of data used in this research is quantitative data. The data source in this research is secondary data. The data collection technique is done by using documentation technique and data analysis using multiple linear analysis. The results of the research partially show that ROA has a positive and insignificant effect on stock prices, total asset turnover has a negative and significant effect on stock prices, while the current ratio and debt to equity ratio have no significant effect on stock prices. The research results simultaneously show the current ratio, ROA, total asset turnover and debt to equity ratio to stock prices. Keywords: CurentRaio, Debt To Equity Ratio, ROA, Stock Price, Total Asset Turnover